A relatively wide-ranged correlation of saturated flow boiling heat transfer within narrow rectangular channel for water. (25th June 2022) - Cao, C.Q.; Kuang, B.; Zhao, Y.; Deng, J.; Ding, S.H.; Wu, D.
Highlights: Database of boiling heat transfer in narrow rectangular channel over a relatively wide parametric range obtained. Corresponding transition of two-phase flow regimes with dominant heat transfer mechanisms observed and discussed. A new, wide-ranged correlation proposed. Abstract: A campaign of tests is performed for saturated boiling heat transfer characteristics of water in narrow rectangular channel. The test matrix covers a relative wide range of conditional parameters and 3142 test data are acquired, screened and selected for study. Meanwhile, visualization test has been conducted with three typical flow patterns, namely isolated bubbly, confined bubbly and irregular annular flows, being observed and identified, each pattern corresponding to a prevailing or a transitional combined boiling heat transfer mode. Study of the data trend indicates that two boiling heat transfer mechanisms, namely nucleate boiling and forced convective evaporation, are either one dominant or two combined transitional during different phases of saturated flow boiling within the channel. With the basic view obtained from the test campaign, and with related parametric effect and sensitivity study, as well as the existing correlation assessment with the test data, a new correlation for the saturated boiling heat transfer is proposed and regressed, which consists a modification factor composing the two basic boiling mechanisms and the transition function between. A preliminary assessment is performed for its statistical and predictive accuracy, from which a relatively satisfactory agreement is drawn. The new correlation applies to a heat flux range of 100 - 2300 k W / m 2, a mass flux range of 500 2000 k g / m 2 · s, a system pressure range of 0.2 5.5 M P a and the equilibrium quality range of 0 0.72 . It might be used, in conjunction with the flow pattern and the related heat transfer mechanism, to predict the saturated boiling heat transfer coefficient over a wide range of heat flux, mass flux and pressures with better accuracy than previous correlations.